Induction immunotherapy followed by surgery for hilar unicentric Castleman disease. Issue 11 (19th April 2022) - Shoji, Fumihiro; Takase, Ken; Kozuma, Yuka; Yamazaki, Koji; Kawauchi, Shigeto; Takeo, Sadanori
Abstract: Castleman disease is a rare disease borne of a B cell lymphoproliferative disorder of uncertain cause. Standard therapy for the unicentric type of Castleman disease localized as a single mass or single lymph‐node station is surgical extirpation. Nevertheless, in the thoracic cavity, unresectable cases or cases of incomplete extirpation of the tumor without lung scarring owing to tumor size/location have been noted. In such cases, lung resection (e.g., lobectomy, pneumonectomy) or additional therapy (immunotherapy, chemotherapy, radiotherapy) after resection is required. However, few instances of patients receiving induction immunotherapy or chemotherapy followed by surgery have been reported. Here, we describe a 21‐year‐old woman with unicentric Castleman disease originating from the left hilum. The tumor seemed to involve/be in contact with the pulmonary vein and bronchus. Tumor location indicated that initial resection was necessary to sacrifice upper and lower pulmonary lobes. To avoid these pulmonary resections, induction therapy followed by surgery was selected. Induction therapy using rituximab was very efficacious. Resection after induction therapy was completed only by tumor extirpation, and resulted in preservation of pulmonary function. Thoracic surgeons might consider induction therapy followed by resection if the tumor is resectable UCAD, but initial resection is needed and sacrifices a large amount of pulmonary function. Abstract : We describe a 21‐year‐old woman with unicentric Castleman disease (UCAD) originating from the left hilum. To avoid these pulmonary resections, induction therapy using rituximab followed by surgery was performed. Optimal treatment of UCAD is complete resection and thoracic surgeons might consider induction therapy followed by resection if the tumor is resectable UCAD, but initial resection is needed and sacrifices a large amount of pulmonary function.